The Relationship between Nutritional Status and Shortness of Breath in Children with Pneumonia at Mappi General Hospital, Indonesia - Naomi Deby Rante Lembang; Mikawati; Rizky Pratiwi (Open Access Indonesian Journal of Medical Reviews, 2023)
The relationship between nutritional status and shortness of breath in childhood pneumonia is an important concern in the management and management of this disease. Poor nutritional status in children can influence their immune system, making them more susceptible to infections such as pneumonia. This study aimed to determine the relationship between nutritional status and the incidence of shortness of breath in children with pneumonia at Mappi General Hospital, Indonesia. This study is a cross-sectional analytic observational study. A total of 49 research subjects were included in this study. Data analysis was carried out using SPSS using univariate and bivariate relationships between nutritional status and the incidence of shortness of breath in pneumonia patients. The majority of pneumonia patients with malnutrition experienced symptoms of shortness of breath compared to pneumonia patients with normal nutrition, p<0.05. There is a significant relationship between poor nutritional status and the incidence of shortness of breath in pediatric patients with pneumonia.